Decision Support System For Selecting Outstanding Students at SD Inpres Lanraki II Using the Weight Product Method - Iskandar, Akbar; Retnawati, Heri; Haryanto, Haryanto; Lukas, Imelda; Sabitu, Kamoru (AL-ISHLAH: Jurnal Pendidikan, 2024)
Education stands as a pivotal driver of national progress, profoundly shaping societal advancement. Within basic education, like elementary schools (SD), the identification and support of exceptional students are paramount. SD Inpres Lanraki II, an educational institution dedicated to nurturing high achievers, underscores this commitment. This study employs the Weight Product method to pinpoint outstanding students. Findings reveal the method's efficacy in streamlining the selection process at SD Inpres Lanraki II, culminating in a top-ranking score of 0.1804, highlighting the selection of exceptional students. The impact is significant, enhancing the institution's ability to cultivate a cohort of high-performing individuals, thus positively influencing its educational landscape. This research not only identifies excellence but also bolsters the school's capacity to foster a generation of academic achievers, reinforcing its educational mission and societal contribution.